2019
DOI: 10.1093/jisesa/iez063
|View full text |Cite
|
Sign up to set email alerts
|

Damselfly (Odonata: Calopterygidae) Population Decline in an Urbanizing Watershed

Abstract: Reduction of terrestrial vegetation and degradation of water quality are among the factors driving insect population decline in growing cities. In this study, we investigated the extent of habitat deterioration, behavioral and physiological responses, and fitness of a damselfly [Hetaerina americana (F.)] population in a semitropical region in central Mexico. The study population was located in a riverine area that crosses a small urban area (Tehuixtla city). We related two habitat variables (tree/shrub covered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Damselflies, being smaller-bodied, have shorter development times, indicating that their greater measured prevalence at urban playas was due to factors other than duration of water availability, such as habitat structure or prey availability. Although damselfly abundance may be reduced at urban wetlands [ 51 ], our findings support those of Perron et al [ 9 ], who found greater damselfly diversity at urban stormwater ponds than at natural areas. This group of insects may be more tolerant of anthropogenic inputs, water quality, and habitat quality than previously considered.…”
Section: Discussionsupporting
confidence: 90%
“…Damselflies, being smaller-bodied, have shorter development times, indicating that their greater measured prevalence at urban playas was due to factors other than duration of water availability, such as habitat structure or prey availability. Although damselfly abundance may be reduced at urban wetlands [ 51 ], our findings support those of Perron et al [ 9 ], who found greater damselfly diversity at urban stormwater ponds than at natural areas. This group of insects may be more tolerant of anthropogenic inputs, water quality, and habitat quality than previously considered.…”
Section: Discussionsupporting
confidence: 90%
“…Our approach accepts some levels of uncertainty for individual species (e.g. a decrease in local abundance) [91], but at a large scale, it provides an estimate of extinction potential that is easy to replicate and that considers phylogenetic non-independence of extinction risk [3,92].…”
Section: Discussionmentioning
confidence: 99%
“…In the current era of defaunation 32 , many organisms are declining rapidly 12,15,16,[33][34][35][36][37] , and especially insects are suffering greatly 6,[8][9][10]13,18,38,39 . This is alarming because we know very little of the fundamental interactions between the majority of species.…”
Section: Discussionmentioning
confidence: 99%
“…Over the very last few decades, multiple studies have pointed to widespread decline among insects 7 . This pattern has been proposed to apply to both species-specific abundances and overall insect biomass and to extend across habitats with highly variable levels of human impact 6 11 , 13 , 18 . This is alarming, given the dominance of insects in terms of diversity 19 and biomass 20 , and the key role of insects in sustaining ecosystem processes and services 5 , 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation